Geologic map of Jamaica - Sawkins, James G. (Boston : B Meisel Lith, 1898)
The diagram represents a Geologic map of Jamaica in 1898 . It uses colour codes to show different parts of the map and where they represent. The codes are as follows: Pleistocene and recent ; Alluvium - Al, Elevated coral reefs - S, Falmouth formation - F ; Teritary ; Pliocene ; Kingston formation - K, Manchioneal formation - M ; Oligene ; Bowden Formation - B, Igneous - I, Cobre, Moneague and Montpelier - Cm ; Eocene ; Cambridge formation - C, Richmond formation - R ; Cretaceous ; Limestones - L, Conglomerates and Tuffs.
Hill - Jamaica 258.
Keywords: Geology -- Jamaica -- Maps; Geology; Jamaica -- Maps; Jamaica; Maps